THE TEACHER’S ROLE IN SUPPORTING MENTAL HEALTH AND WELL-BEING - Rustamova, Sevinch (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This paper highlights the teacher’s role in fostering student motivation and supporting mental health in classrooms. It emphasizes the need for creating engaging lessons, showing empathy, and building supportive relationships. By addressing both academic and emotional needs, teachers can improve students’ well-being and learning outcomes.